Penyuluhan Pengelolaan Keuangan Rumah Tangga Berdasarkan Prinsip Syariah - Ruhliandini, Putri Zafira; Aditya, Fajar Aditya; Fatimah, Rista Amelia (Ma'soem University, 2025)
The background of this activity is the low level of understanding among the community, especially housewives in Cibungur Village, regarding the principles of sharia-based financial management. This condition leads to many families lacking clear budget planning, facing difficulties in managing income and expenses (including not recording them), and having limited knowledge of sharia investment products, which results in potential financial instability. The purpose of this outreach is to provide comprehensive understanding of the concept of sharia household financial management, ranging from budget planning and expenditure prioritization to sharia-compliant investment, with the hope of creating financial independence and achieving a sakinah family. The community service partner is the community of Cibungur Village, Rancakalong District, Sumedang Regency. The method used is transformative Participatory Action Research (PAR), with the counseling being evaluated using the CIPP model (Context, Input, Process, Product). The initial findings show that the financial literacy of the residents is still minimal, evidenced by the habit of storing assets in the form of cash or gold jewelry due to limited access to modern sharia instruments. However, the counseling activity, conducted on August 02, 2025, received a very positive response, proven by the high enthusiasm and active communication of the participants during the discussion and Q&A sessions. This interaction indicates that participants actively constructed their new knowledge, suggesting that the community service activity successfully increased awareness and understanding of sharia household financial management.